2021
DOI: 10.1016/j.neurobiolaging.2021.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the inflammatory S100-A9/MRP14 protein does not influence survival in hSOD1G93A ALS mice

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Transthyretin (TTR) was shown to be dysregulated in ALS compared to control spinal cord samples [60] and Beta 2-microglobulin (B2M) has shown differential RNA expression in the peripheral white blood cells of ALS patients compared to control [61], making them potential biomarkers. S100-A9 mRNA levels were increased at end-stage ALS but deleting it in a mouse model had no impact on motor neuron survival and slightly accelerated symptoms [62]. In one study, S100B was found to be upregulated in ALS spinal cord samples [63], but in another, levels decreased with disease progression [64].…”
Section: Key Proteinsmentioning
confidence: 99%
“…Transthyretin (TTR) was shown to be dysregulated in ALS compared to control spinal cord samples [60] and Beta 2-microglobulin (B2M) has shown differential RNA expression in the peripheral white blood cells of ALS patients compared to control [61], making them potential biomarkers. S100-A9 mRNA levels were increased at end-stage ALS but deleting it in a mouse model had no impact on motor neuron survival and slightly accelerated symptoms [62]. In one study, S100B was found to be upregulated in ALS spinal cord samples [63], but in another, levels decreased with disease progression [64].…”
Section: Key Proteinsmentioning
confidence: 99%
“…(iii) phase III, representing the time window between the mean day in which mice lost 5% of body weight and the mean day in which they lost 10% of body weight (Ribon et al, 2021).…”
Section: Body Weight Lossmentioning
confidence: 99%